Pengaruh Kualitas Pelayanan Terhadap Loyalitas Tamu Di Daima Hotel Padang - Mulawarman, Rian; Susanti, Retnaningtyas (CV. ITTC INDONESIA, 2024)
The goal of this research is to examine the impact of service quality on guest loyalty at Daima Hotel Padang. Guest loyalty is an important factor in maintaining and increasing the number of visits, especially in the hospitality industry which is highly dependent on customer satisfaction. However, the data shows that less than optimal service quality can have an impact on decreasing guest loyalty at this hotel. Data for this study is gathered quantitatively using dispersed questionnaires to 303 hotel guests as respondents. Statistical tests were used for data analysis, including normality, linearity, homogeneity, and simple regression tests with a significance level of 0.05. The study's findings show that visitor loyalty is significantly impacted by service quality, with a positive contribution to increasing loyalty. with a positive contribution to increasing loyalty. This implies that the better the quality of the services offered by the hotel, the higher the level of guest loyalty. This research is anticipated to offer practical recommendations for Daima Hotel Padang management in improving more effective service strategies to build and maintain guest loyalty.